2015
DOI: 10.1038/srep12016
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin inhibits IL-1 secretion and non-canonical inflammasome activation

Abstract: Deregulation of inflammasome activation was recently identified to be involved in the pathogenesis of various inflammatory diseases. Although macrolide antibiotics display well described immunomodulatory properties, presumably involved in their clinical effects, their impact on inflammasome activation has not been investigated. We compared the influence of macrolides on cytokine induction in human monocytes. The role of intracellular azithromycin-accumulation was examined by interference with Ca++-dependent up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 45 publications
5
48
0
2
Order By: Relevance
“…Azithromycin treatment resulted in no change in sputum concentration of IL‐8, IL‐17A or TNF‐α, whereas IL‐1β levels decreased significantly. IL‐1β is a potent pro‐inflammatory cytokine which induces pulmonary neutrophil airway inflammation and airway damage in mice, and the reduction in IL‐1β with azithromycin is consistent with findings from murine studies and suggests a mechanism for decreased neutrophilic inflammation.…”
Section: Discussionsupporting
confidence: 77%
“…Azithromycin treatment resulted in no change in sputum concentration of IL‐8, IL‐17A or TNF‐α, whereas IL‐1β levels decreased significantly. IL‐1β is a potent pro‐inflammatory cytokine which induces pulmonary neutrophil airway inflammation and airway damage in mice, and the reduction in IL‐1β with azithromycin is consistent with findings from murine studies and suggests a mechanism for decreased neutrophilic inflammation.…”
Section: Discussionsupporting
confidence: 77%
“…However, we showed that (at a 6 μM concentration) the reduction in MMP-9 levels upon treatment with minocycline and azithromycin was independent of NFκB. Specifically, NF-κB-independent reduction of LPS-induced IL-1β secretion was previously described for azithromycin [40] Moreover, treatment of human monocytes with azithromycin had an impaired induction of caspase-4 which was recently described as a new intracellular LPS sensor [47, 48]. Indeed, pharmacokinetics of macrolide antibiotics such as azithromycin show a predominant accumulation in white blood cells [49].…”
Section: Discussionmentioning
confidence: 55%
“…At a concentration of 6 μM neither minocycline nor azithromycin affected NF- κB phosphorylation in comparison to cells only stimulated with LPS (Fig 7A). Among cytokines which can induce MMP-9 expression [39], IL-1β was previously reported to be reduced by azithromycin, independently of NF- κB [40]. Therefore, we next evaluated the presence of IL-1 β in cell supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…The drug is widely used in vitro as an inhibitor of NLRP3 inflammasome. The introduction of other macrolides including erythromycin, clarithromycin and azithromycin appears to have similar anti‐inflammatory and immunomodulatory properties .…”
Section: Macrolidesmentioning
confidence: 99%
“…The introduction of other macrolides including erythromycin, clarithromycin and azithromycin appears to have similar anti‐inflammatory and immunomodulatory properties . The macrolide azithromycin has also been shown to have anti‐inflammatory effects in bronchiectasis, as it enhances the clearance of apoptotic cells, such as neutrophils, by improved macrophage phagocytic function .…”
Section: Macrolidesmentioning
confidence: 99%